Synergies and Trade-Offs in the Sustainable Development Goals—The Implications of the Icelandic Tourism Sector - David Cook; Nína Saviolidis; Brynhildur Davíðsdóttir; Lára Jóhannsdóttir; Snjólfur Ólafsson (Sustainability, 2019)
The development of major economic sectors can provide the bedrock on which long-lasting national economic prosperity is formed. Iceland’s tourism sector is an example of a rapidly expanded industry in recent years, to the extent that it has become the largest sectoral contributor to the nation’s economy. The growth of the sector has led to a number of sustainability impacts, thus presenting opportunities and challenges in terms of meeting the 17 Sustainable Development Goals (SDGs) of the United Nations. Using the case study of Iceland, this paper aims to advance the conceptual understanding of the synergies and trade-offs between a nation’s tourism sector and performance across the 169 targets of the SDGs. Empirical results were derived from four theme-based focus groups comprised of expert participants, who were tasked with completing scoresheets concerning their perception of the extent of synergies and trade-offs for each target. The majority (126 in number) of the mean scoresheet outcomes for the SDG targets revealed neither synergies nor trade-offs. However, 32 synergies and 11 trade-offs were identified. Many of the target synergies related to new economic opportunities, such as jobs, employment, and training for young people. Target trade-offs tended to be environmental and social. In particular, concern was voiced about the greenhouse gas emissions of the Icelandic tourism sector, which derives from international aviation, cruise ships, and rental car usage. The outcomes of this study are of particular relevance to tourism companies, policy-makers, and governance institutions, all of whom are increasingly endeavouring to link their activities with the fulfilment of the SDGs, maximising synergies, mitigating the extent of any potential trade-offs, and potentially transforming trade-offs into synergies. Furthermore, the results are likely of interest to academics focused on researching the broad sustainability impacts of economic sectors and their contribution to meeting the visionary goals of the SDGs.